2017
DOI: 10.1101/217240
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chronic ethanol ingestion impairs Drosophila melanogaster health in a microbiome-dependent manner

Abstract: The microbiome can modulate the interaction between animals and their environment. In particular, intestinal microbes play a strong role in shaping how animals respond to their diets, and especially dietary toxins. In this study, we investigated how the microbiome affects the interaction between the fruit fly Drosophila melanogaster and ingested ethanol. D. melanogaster naturally feeds on fermenting fruits and therefore commonly ingests ethanol. This dietary ethanol is generally considered to be a toxin, but i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…The impact of substance abuse on the microbiota has been most extensively studied in alcohol abuse. Research has linked alterations in gut microbiota during alcohol consumption to increased intestinal permeability and hepatic inflammation (168,227,273,914,925,1086,1087,1641), but a reduced gut microbiome can also protect from alcohol-induced neuroinflammation resulting in the alteration of intestinal and brain inflammasome expression (926). Preclinical supplementation with L. rhamnosus GG has been shown to lessen the severity of alcoholic hepatitis (227).…”
Section: G Addictionmentioning
confidence: 99%
“…The impact of substance abuse on the microbiota has been most extensively studied in alcohol abuse. Research has linked alterations in gut microbiota during alcohol consumption to increased intestinal permeability and hepatic inflammation (168,227,273,914,925,1086,1087,1641), but a reduced gut microbiome can also protect from alcohol-induced neuroinflammation resulting in the alteration of intestinal and brain inflammasome expression (926). Preclinical supplementation with L. rhamnosus GG has been shown to lessen the severity of alcoholic hepatitis (227).…”
Section: G Addictionmentioning
confidence: 99%
“…Chandler observed that dietary ethanol leads to a dose-dependent decrease of life span in germfree flies, while conventionally reared flies have stable life spans at low and moderate ethanol concentrations. Chandler found that ethanol also alters some immune markers but only in conventionally reared flies (31), which may parallel findings in humans that ethanol-induced inflammation and alcoholic liver disease are influenced by the microbiome. Reed Stubbendieck (University of Wisconsin-Madison, Madison, WI) presented "Bacterial Competition Mediated by Siderophore Production among the Human Nasal Microbiota."…”
Section: Ecology and Evolution Of Microbe-host Interactionsmentioning
confidence: 52%